American portrait : the story of us, told by us (HarperOne, an imprint of HarperCollinsPublishers, 2021)
"Based on the popular and groundbreaking PBS multiplatform documentary project, this is an inspiring and striking photographic portrait that brilliantly captures the tumultuous, historic year that was 2020. American Portrait offers an intimate look at what it really means to be an American today, revealed through the stories of ordinary people and in their own voices. Told by people of all ages, orientations, and walks of life, these unique stories of joy, adversity, love, sacrifice, grief, sharing, triumph, and grace--centered on the themes of family, work, fun, faith, community, and more--illuminate the struggles, hopes, dreams, and convictions of Americans today. American Portrait is a vital and ultimately hopeful reminder that what we all share is much greater and enduring than what may divide us"--Page 4 of cover.